2019
DOI: 10.3171/2018.2.jns173138
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in traumatic brain injury patients with midline shift: a secondary analysis of the Phase 3 COBRIT clinical trial

Abstract: OBJECTIVE Following traumatic brain injury (TBI), midline shift of the brain at the level of the septum pellucidum is often caused by unilateral space-occupying lesions and is associated with increased intracranial pressure and worsened morbidity and mortality. While outcome has been studied in this population, the recovery trajectory has not been reported in a large cohort of patients with TBI. The authors sought to utilize the Citicoline Brain Injury Treatment (COBRIT) trial to analyze patient recovery over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
0
22
0
2
Order By: Relevance
“…In a secondary analysis of the Citicoline Brain Injury Treatment (COBRIT) trial, Puffer et al demonstrated worsening outcomes as midline shift increased from no shift to 1-5 mm, further worsening at shifts of 6-10 mm, and significantly poor outcomes with shifts > 10 mm, as expected. 26 However, the trial was inclusive of all TBI patients and not limited to elderly patients undergoing surgical evacuation of atSDH. Nonetheless, increasing midline shift at presentation correlates with worse outcomes, but like all individual patient characteristics, this imaging variable should not be used alone as a prognostic factor but should be interpreted with the overall injury severity and comorbidity burden of each patient encountered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a secondary analysis of the Citicoline Brain Injury Treatment (COBRIT) trial, Puffer et al demonstrated worsening outcomes as midline shift increased from no shift to 1-5 mm, further worsening at shifts of 6-10 mm, and significantly poor outcomes with shifts > 10 mm, as expected. 26 However, the trial was inclusive of all TBI patients and not limited to elderly patients undergoing surgical evacuation of atSDH. Nonetheless, increasing midline shift at presentation correlates with worse outcomes, but like all individual patient characteristics, this imaging variable should not be used alone as a prognostic factor but should be interpreted with the overall injury severity and comorbidity burden of each patient encountered.…”
Section: Discussionmentioning
confidence: 99%
“…The median ISS was [25][26]. The most common presenting GCS score was 13-15 (1722 [73%]), followed by 3-8 (449 [19.1%]) and 9-12 (177 [7.5%]).…”
Section: Baseline Injury Severity Characteristicsmentioning
confidence: 99%
“…Minimal brain swelling showing only sulci effacement without affecting a patient's prognosis was excluded. Severe brain swelling was defined as more than 10 mm of mid-line shifting (12).…”
Section: Imaging Interpretationmentioning
confidence: 99%
“…Kết quả này cũng phù hợp với tác giả Lê Thị Yến Phụng ghi nhận tỷ lệ bệnh nhân có dập não là 52.6%, xuất huyết dưới nhện là 31.6%, tụ máu dưới màng cứng 39.5% [1]. Nghiên cứu của chúng tôi nhận thấy dịch chuyển đường giữa trên phim chụp CT scan sọ não chiếm tỷ lệ 20.44%; phù hợp với Puffer và cs (2018) khi đánh giá mối liên quan giữa kết cục lâu dài và mức độ lệch đường giữa trên phim chụp CT sọ não ban đầu đã ghi nhận: ở nhóm bệnh nhân đánh giá sau CTSN 30 ngày với 892 bệnh nhân nghiên cứu có 697 bệnh nhân không có dịch chuyển đường giữa [8], (tỷ lệ số bệnh nhân có di lệch đường giữa tương ứng là 21.86%). Tỷ lệ số bệnh nhân CTSN không có hình tổn thương não trên phim CT sọ não (8.44%), thấp hơn nhiều so với kết quả nghiên cứu của tác giả Trương Phước Sở (2009) (80.01%) [2].…”
Section: Bảng 4 Thời Gian Vào Giấc Ngủ Trung Bình Và Thời Gian Ngủ đượC Trung Bình Mỗi đêMunclassified
“…Số liệu bảng 6: Tỷ lệ mất ngủ cấp tính ở bệnh nhân CTSN có Dập và/hoặc xuất huyết não cao hơn tỷ lệ này ở nhóm bệnh nhân CTSN không có Dập và/hoặc xuất huyết não có ý nghĩa thống kê. Mặt khác Puffer và cs khi đánh giá mối liên quan giữa kết cục dài hạn và mức độ di lệch đường giữa trên các bệnh nhân CTSN nhận thấy rằng các bệnh nhân có mức di lệch đường giữa dưới 10 mm trên phim chụp CT scan sọ não lúc nhập viện cải thiện đáng kể kết quả chức năng so với những bệnh nhân có mức di lệch đường giữa trên 10mm [8]. Nghiên cứu của chúng tôi cũng ghi nhận rằng những bệnh nhân có lệch đường giữa có tỷ lệ mất ngủ cấp tính cao hơn so với các bệnh nhân không lệch đường giữa.…”
Section: Bảng 4 Thời Gian Vào Giấc Ngủ Trung Bình Và Thời Gian Ngủ đượC Trung Bình Mỗi đêMunclassified